MİLLETLERARASI TAHKİMDE YENİ GELİŞMELER: TAHKİM YARGILAMASI SÜRECİ VE MASRAFLARININ AZALTILMASI - (:unkn) unknown (My University, 2013)
Kullanıcıların milletlerarası tahkimden bekledikleri en önemli iki husus davanın hızlı ve mümkün olduğunca az masrafı bir şekilde kabul edilebilir, mantıklı bir sonuca ulaşabilmesidir. Bu iki önemli hedefe ulaşabilmek için tanıkların nasıl dinleneceği, duruşmanın nasıl olması gerektiği gibi detaylar içermeyen tahkim kurallarının doktrin ve milletlerarası tahkim kurumlarının hazırladıkları öneri niteliğindeki raporlarla desteklenmelidir. Çalışmamızda tahkim yargılaması masrafarı ile ilgili genel bir bilgi verildikten sonra bahsi geçen raporlar ve doktrin ışığında dava yönetim teknikleri tahkim yargılaması süreci ve masrafarının azaltılması açısından irdelenecektir.

To reach an acceptable resolution as quickly and as inexpensively as possible are the most important issues expected by users from International Arbitration. In order to reach the sated goal, the rules of arbitration revised which do not concern procedure details regarding hearing of witnesses, case management etc., shall be supported by doctrine and advisory reports prepared by international arbitration institutions. In this study, after general explanations regarding costs of arbitration, the techniques advised by aforementioned reports and doctrine are examined with the purpose of avoiding the same mistakes over and over again during arbitration process and of reducing duration  of  arbitration proceedings and costs of arbitration.
International Arbitration Recent Develop ments: Reducing the Duration of and the Costs in Arbitration Proceedings
Keywords: Hukuk